MODEL IMPLEMENTASI LOGIKA FUZZY UNTUK PENILAIAN KINERJA KARYAWAN IT SUPPORT - Sumanto Sumanto; Ade Christian; Ahmad Yani; Karlena Indriani; Sumarna Sumarna; Hafis Nurdin (Jurnal Sistem Informasi dan Informatika (Simika), 2022)
Human resources are the most valuable asset in a company. Employee performance is one of the company's benchmarks in assessing the productivity of these assets. Methods in measuring employee performance can be done in various forms, one of which is using the fuzzy logic method. Fuzzy Mamdani is a fuzzy inference method that provides rules that must be passed before carrying out the process of determining the final value. There are three main criteria that will be analyzed in this study, namely attendance, quality of work and communication. Each of these criteria has a value obtained from the average value of several elements. The final result after going through the employee data analysis process is the average weighted value. Conclusions that can be drawn as the basis for employee performance and the results can be seen from the order of values, starting from the highest to the lowest. MATLAB or what we call it (Matrix Laboratory) is a program for analyzing and computing numerical data, and MATLAB is also an advanced mathematical programming language, which was formed on the premise of using the properties and forms of matrices. Graphical User Interface (GUI) is a visual media that makes users give certain commands on the computer without typing the command, but using the available images.